The history of development of Pharmacopoeia standards quality biological drugs and methods of tests in Russia - T. M. Kargina; I. G. Osipov; E. I. Sakanyan; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The Russian system of standardization of HP including biological medicines is based on the State Pharmacopoeia of the Russian Federation numbering more than the 250th summer history of the development. Requirements of general the farmakopoeia and the farmakopoeia of articles included in the State Pharmacopoeia of the Russian Federation are obligatory for all organizations which are engaged in the territory of the Russian Federation in production, production, quality control, storage and use of medicines. Historical development the farmakopoeia of the quality standards on biological medicines is reflected in article, starting with the first publications of articles editions (1910) and to GF Programme of the Russian Federation editions (2015) in which are provided are included in GF VI of Russia 57 OFS and 56 FS on the biological medicines allowing to provide standardization of requirements to their quality. Further enhancement and development of various directions in the immunobiology, immunobiological technologies which are based on a joint of immunology and molecular biology, and also genetic engineering and as a result of it, development of new BLP requires further development and the standardization of these HP guaranteeing their quality at all stages of lifecycle.